MENGENAL LARAS MELALUI PROSES BELAJAR GAMELAN PADA SISWA SEKOLAH DASAR AL-ISLAM 2 JAMSAREN SURAKARTA - Isti Kurniatun (Institut Seni Indonesia Surakarta, 2016)
Nowadays, Students of Elementary school are less interested in Larasan Gamelan (melody of music).It caused by limited time for them to knowing and studying music melody. PKM activities conductedby Indonesian Art Institute of Surakarta especially at Al-Islam Surakarta Elementary School haveprovided a chance for knowing and studying music melody. Although there are many challengesand inhibitors, music melody conservation must to do. Method for introducing larasan (melody)among student at elementary school needs for improvement to stimulate their interest. The finalaim of this activity is give musical richness for students.Key words : laras, studying, interest.